Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1175/2008jas2453.1
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling Study of Typhoon Nari (2001) at Landfall. Part I: Topographic Effects

Abstract: Although there have been many observational and modeling studies of tropical cyclones, understanding of their intensity and structural changes after landfall is rather limited. In this study, several 84-h cloudresolving simulations of Typhoon Nari (2001), a typhoon that produced torrential rainfall of more than 1400 mm over Taiwan, are carried out using a quadruply nested-grid mesoscale model whose finest grid size was 2 km. It is shown that the model reproduces reasonably well Nari's kinematic and precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 44 publications
2
66
0
Order By: Relevance
“…Another example was the severe rainfall of more than 1000 mm associated with the moderate southwest bound Typhoon Nari (2001). This typhoon has been well simulated by MM5 at a high horizontal resolution (e.g., Huang et al 2005;Yang et al 2008Yang et al , 2011. Recently, Wu et al (2009) successfully simulated an intense rainfall event associated with the northeast bound Typhoon Babs (1998) as its outer cyclonic flow confronted the winter monsoon flow in north Taiwan.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another example was the severe rainfall of more than 1000 mm associated with the moderate southwest bound Typhoon Nari (2001). This typhoon has been well simulated by MM5 at a high horizontal resolution (e.g., Huang et al 2005;Yang et al 2008Yang et al , 2011. Recently, Wu et al (2009) successfully simulated an intense rainfall event associated with the northeast bound Typhoon Babs (1998) as its outer cyclonic flow confronted the winter monsoon flow in north Taiwan.…”
Section: Introductionmentioning
confidence: 95%
“…The interaction between the typhoon vortex and the CMR which cause track deviations and different rainfall activities has long been a challenging problem tackled by numerous studies (e.g., Chang 1982;Bender et al 1987;Yeh and Elsberry 1993a, b;Lin et al 2002Lin et al , 2005Wu et al 2002Wu et al , 2009Chiao and Lin 2003;Huang et al 2005;Jian and Wu 2008;Yang et al 2008Yang et al , 2011Chien and Kuo 2011). The intense flow associated with a typhoon striking Taiwan tends to produce persistent heavy rains over the steep windward slopes, a situation favorable for a possible "terrain-locking" mechanism that somewhat reduces the difficulty in obtaining rainfall predictability (Wu et al 2002Lin et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that damages are strongly related to the location of the typhoon's landfall and interactions between its circulation and the CMR (Brand and Blelloch 1974;Wu and Kurihara, 1996;Wu and Kuo, 1999;Lin et al, 2001;Chien et al, 2008;Ge et al, 2010). Previous studies pointed out that enormous amounts of rainfall occur and are enhanced due to mountain lifting when a typhoon passes over the CMR (Wu and Kuo, 1999;Lin et al, 2001Wu et al, 2002;Yang et al, 2008). Moreover, it is common that the strong southwesterly flow follows the departure of an invading typhoon and brings heavy rainfall over central or Southern Taiwan Chien et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For the sensitivity experiments, the surface topographic data were changed as in Yang et al (2008). The input surface topo- ysis: TMPA-RT) for the period during the typhoon hit Mindanao Island, and Figs.…”
Section: Control Run a Validation Of Model Outputmentioning
confidence: 99%
“…According to Wu et al (2002), both of 6.7 km and 2.2 km grid spacing resolution is similarly sufficient to reproduce the rainfall distribution by the orographic effect in Taiwan. As Yang et al (2008) showed, sensitivity experiments with different terrains are effective to investigate topographic influences on land-falling typhoons.…”
Section: Introductionmentioning
confidence: 99%